EFEKTIVITAS INOVASI CDR (CARI, DATA, REKAM) RESQUE JEMPUT BOLA DI DINAS KEPENDUDUKAN KABUPATEN PINRANG - Reza Fahrezy, Andi Yusril; Haerana, Haerana; Khaerah, Nur (Universitas Muhammadiyah Makassar, 2023)
The purpose of this study was to find out how the Effectiveness of CDR Service Innovation (Search, Data, Record) Resque Pickup Balls at the Population and Civil Registration Service of Pinrang Regency. The type and type of research is a descriptive qualitative approach that will provide an overview or phenomena and problems that occur. Data collection techniques are through observation, media review, interviews and documentation. The results of research conducted at the Office of Population and Civil Registration there are three criteria, namely: Achievement of Goals, Integration and Adaptation. Based on the results of the study, it shows that the effectiveness of Resque CDR services in achieving the goals has been going well and does not take a long time according to the standard service time and has achieved the specified service goals. However, in the socialization process, they only coordinate with the local government and there are still people who do not know about the Resque CDR service, so there are still many who do not know about the Resque CDR service.